Private enterprise in China - Garnaut, Ross; Song, Ligang; Yao, Yang; Wang, Xiaolu (PANDORA electronic collection., 2012)
"The book reports and interprets results from a detailed study of the contemporary private sector in China. It is based on the Technical Report on Private Enterprise Development in China commissioned by the International Finance Corporation (IFC) and the State Economic and Trade Commission (SETC) of the People's Republic of China. The research was undertaken by a team from the Australian National University and Peking University."--Preface.